Baseline assessment of the WHO/UNICEF/UNFPA maternal and newborn quality-of-care standards around childbirth: Results from an intermediate hospital, northeast Namibia - Siseho, Gloria Mutimbwa; Mathole, Thubelihle; Jackson, Debra (Frontiers in Pediatrics, 2023)
Background: Quality-of-care around childbirth can reduce above half of stillbirths, and newborn deaths. Northeast Namibia’s neonatal mortality is higher than the national level. Yet no review exists on the quality provided around childbirth. This paper reports on baseline assessment for implementing WHO/UNICEF/UNFPA quality measures around childbirth. Methods: A mixed methods research design was used to assess quality-of-care around childbirth. To obtain good saturation and adequate women voices, we purposively sampled the only high-volume hospital in northeast Namibia; observed 53 women at admission, of those 19 progressed to deliver on the same day/hours of data collection; interviewed 20 staff and 100 delivered women at discharge. The sampled hospital accounted for half of all deliveries in that region and high (27/1000) neonatal mortality rate above national (20/1000) level. We systematically sampled every 22nd delivery until the 259 mother-baby pair was reached. Data was collected using Every Mother Every Newborn assessment tool, entered, and analyzed using SPSS V.27. Descriptive statistics was used, and results summarized into tables and graphs. Results: We reviewed 259 mother-baby pair records. Blood pressure, pulse, and temperature checking were done in 98% of observed women and 90% of interviewed women at discharge. Above 80% of human and essential physical resources were adequately available. Gaps were identified within the WHO/UNICEF/UNFPA quality standard1, quality statement on routine postpartum and postnatal newborn care (1.1c). Also, within standard 4,5 and 6 on provider-client interactions (4.1), information sharing (5.3) and companionship (6.1). Only 45% of staff received in-service training/refresher on postnatal care and breastfeeding. Most mothers were not informed about breastfeeding (52%), postpartum care and hygiene (59%) and family planning (72%). On average, 49% of newborn postnatal care interventions (1.1c) were practiced. Few mothers (0-12%) could mention any newborn danger sign. Conclusion: This is the first Namibia study to assess WHO/UNICEF/UNFPA quality-of-care measures around childbirth. Measures of provider-client interactions, and information sharing identified significant deficiencies in this aspect of care which negatively affected client experience of care. To achieve reductions in neonatal death improved training in communication skills to educate clients are likely to have a major positive and relatively low cost impact.